Síntese e caracterização de catalisadores Ni/Al2o3 dopados com Zn e Ce para reforma a vapor do metano - Monteiro, Cláudio Vinicius Barbosa (2016)
The current world lives in a conjuncture of growing increase of the demand for clean and cheap energy and the production of hydrogen (H2) from hydrocarbons obtained from renewable sources, such as the biogas, has been proving to be a viable alternative to supply this energy necessity. In the execution of this reform, there are utilized porous materials with some kind of metal deposited under its surface. The noble metals are the most recommended, but due to their cost, its synthesis process reaches a high price, making it impeditive. In this context, Nickel appears as a metal with good features for the reform, and with an affordable cost. However, during the process it occurs the effect of coking, or formation of carbon above the surface of the support, decreasing therefore its activity. In order to bypass this problem, many authors have suggested the utilization of low-concentration metals, or doping, which increase the conversion and selectivity of this type of catalyst. With the intention of evaluating the effects of doping of Ni/Al2O3 catalysts with Ce and Zn, nine Ni/Al2O3 catalysts were synthesized via humid impregnation with Ni at 5%, 8% and 15%. One third of these catalysts were doped with 0,5% of Ce, and one third with 0,5% of Zn. The catalysts were characterized by TGA, BET area, Atomic Absorption Spectroscopy, IR Spectroscopy, DRX and TPR. It was observed that the concentrations at 8% and 15% of Ni resulted in a greater interaction between AI/Ni. The characterizations showed that for one concentration of Ni at 15% the doping resulted in an improvement on the metal dispersion over the catalyst's surface, with favorable impacts on the development of the catalyst observed in a reactor which differential is at 800ºC, in the molar ratio of CH4/H2O = 1. The yield and selectivity results indicated an improvement for catalysts doped with Zinc and Ceria.